Labor-Management Relations in Autocratic Regimes - Fang Lee Cooke; Geoffrey Wood (Global Labor Organization (GLO), 2022)
This chapter examines contemporary labor-management relations in autocratic regimes, drawing on two sets of countries, namely transitional peripheral economies in Central Asia (Uzbekistan and Turkmenistan) and hierarchical market economies in Latin America (Colombia and Honduras), for analysis. We discuss the political economy, work, and labor relations of these countries, highlighting the role of the state, business, and international non-government organizations. We also take into account the impact of large-scale (often in millions) migration of workers both internally within the country and cross-border. It is important to note that, just as there are different types of democratic systems, there are also different types of autocratic regimes with distinct political, economic, and social policy orientations, and this directly impacts the nature of labor relations. Under Latin American right-wing authoritarianism, a primary focus is on supporting a relatively small property-owning elite, and any countervailing worker power is seen as a direct attack on the latter. Even if workers have employment rights under the law, this zero-sum game view frequently results in extra-legal attacks on worker activists and their representatives, making union organization an extremely dangerous business. In contrast, the Central Asian autocracies, business elites are tied up within extended clan networks. Especially within Uzbekistan, a much closer emphasis has been placed on the provision of a critical mass of jobs as a means of buying political stability. Unions have been afforded a place in the system both for historical reasons and as proof of an ability to create a critical mass of decent work; at the same time, there is little room for union autonomy.
Keywords: E24; E26; F23; F66; J08; 330; autocratic regimes; labor-management relations; Central Asia; Latin America; trade unions; international labor organisations